Viruses of plants - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Viruses of plants by A A Brunt. K Crabtree, M J Dallwitz, A J Gibbs and L Watson 1996 1484pp price UKL99 50 ISBN 0 85198 794X